Plasma Rich in Growth Factors in Bone Regeneration: The Proximity to the Clot as a Differential Factor in Osteoblast Cell Behaviour - Eduardo Anitua; Mar Zalduendo; Roberto Tierno; Mohammad Hamdan Alkhraisat (MDPI AG, 2024)
The osteogenic differentiation process, by which bone marrow mesenchymal stem cells and osteoprogenitors transform into osteoblasts, is regulated by several growth factors, cytokines, and hormones. Plasma Rich in Growth Factors (PRGF) is a blood-derived preparation consisting of a plethora of bioactive molecules, also susceptible to containing epigenetic factors such as ncRNAs and EVs, that stimulates tissue regeneration. The aim of this study was to investigate the effect of the PRGF clot formulation on osteogenic differentiation. Firstly, osteoblast cells were isolated and characterised. The proliferation of bone cells cultured onto PRGF clots or treated with PRGF supernatant was determined. Moreover, the gene expression of Runx2 (ID: 860), SP7 (ID: 121340), and ALPL (ID: 249) was analysed by one-step real-time quantitative polymerase chain reaction (RT-qPCR). Additionally, alkaline phosphatase (ALPL) activity determination was performed. The highest proliferative effect was achieved by the PRGF supernatant in all the study periods analysed. Concerning gene expression, the logRGE of Runx2 increased significantly in osteoblasts cultured with PRGF formulations compared with the control group, while that of SP7 increased significantly in osteoblasts grown on the PRGF clots. On the other hand, despite the fact that the PRGF supernatant induced ALPL up-regulation, significantly higher enzyme activity was detected for the PRGF clots in comparison with the supernatant formulation. According to our results, contact with the PRGF clot could promote a more advanced phase in the osteogenic process, associated to higher levels of ALPL activity. Furthermore, the PRGF clot releasate stimulated a higher proliferation rate in addition to reduced SP7 expression in the cells located at a distant ubication, leading to a less mature osteoblast stage. Thus, the spatial relationship between the PRGF clot and the osteoprogenitors cells could be a factor that influences regenerative outcomes.